Daily to Centennial Behavior of Aseismic Slip Along the Central Section of the North Anatolian Fault - Jolivet, R.; Jara, J.; Dalaison, M.; Rouet-Leduc, B.; Ozdemir, A.; Dogan, U.; Cakir, Z.; Ergintav, S.; Dubernet, P. (AMER GEOPHYSICAL UNION, 2023)
Slow, aseismic slip plays a crucial role in the initiation, propagation, and arrest of large earthquakes along active faults. In addition, aseismic slip controls the budget of elastic strain in the crust, hence the amount of energy available for upcoming earthquakes. The conditions for slow slip include specific material properties of the fault zone, pore fluid pressure, and geometrical complexities of the fault plane. Fine scale descriptions of aseismic slip at the surface and at depth are key to determine the factors controlling the occurrence of slow, aseismic versus rapid, seismic fault slip. We focus on the spatial and temporal distribution of aseismic slip along the North Anatolian Fault, the plate boundary accommodating the 2 cm/yr of relative motion between Anatolia and Eurasia. Along the eastern termination of the rupture trace of the 1944 M7.3 Bolu-Gerede earthquake lies a segment that slips aseismically since at least the 1950s. We use Sentinel 1 time series of displacement and GNSS data to provide a spatio-temporal description of the kinematics of fault slip. We show that aseismic slip observed at the surface is coincident with a shallow locking depth and that slow slip events with a return period of 2.5 years are restricted to a specific section of the fault. In the light of historical measurements, we discuss potential rheological implications of our results and propose a simple alternative model to explain the local occurrence of shallow aseismic slip at this location.
Keywords: North Anatolian fault; aseismic slip; InSAR; SAN-ANDREAS FAULT; ISMETPASA SEGMENT; CREEPING SECTION; FLUID PRESSURE; SILENT SLIP; TURKEY; SUBDUCTION; EARTHQUAKE; EVENT; Geochemistry & Geophysics